2010
DOI: 10.1007/s11270-010-0434-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Ozone Sensitivity at Different NPK Levels of Three Tropical Varieties of Mustard (Brassica campestris L.): Photosynthetic Pigments, Metabolites, and Antioxidants

Abstract: The effects of ambient O 3 at two different levels of nitrogen, phosphorus, and potassium, (recommended and 1.5 times the recommended NPK) on three tropical varieties of mustard (Brassica campestris L. var. Kranti, Aashirwad and Vardan) were explored to unravel the mechanism of protection under higher NPK level at a rural experimental site using open top chambers. Ambient O 3 concentrations ranged from 27.7 to 59.04 ppb. Lipid peroxidation, antioxidative enzymes, and metabolites were higher, whereas photosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Phenolic compounds in mustard varieties were determined by different analytical methods. Among them, a spectrophotometric method using the Folin–Ciocalteu reagent has often been proposed for assaying total phenolics content (2.62–36.5 mg g −1 ) in mustard samples . However, for separation, identification and quantification of the individual phenolic compounds chromatographic techniques are required .…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds in mustard varieties were determined by different analytical methods. Among them, a spectrophotometric method using the Folin–Ciocalteu reagent has often been proposed for assaying total phenolics content (2.62–36.5 mg g −1 ) in mustard samples . However, for separation, identification and quantification of the individual phenolic compounds chromatographic techniques are required .…”
Section: Introductionmentioning
confidence: 99%
“…Singh observed a significant increase in oxidative stress in mustard under exposure to ozone (O 3 ), leading to a significant decrease in the photosynthetic pigment and soluble protein content in leaves, while strengthening antioxidant defense systems to resist its effects (Singh et al, 2011;Singh et al, 2020). In summary, PM can enter plants through stomata and affect them by inducing the formation of reactive oxygen species and redox-sensitive signaling pathways that exert toxicity through the synergistic effects of oxidative stress and inflammation (Michael et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…But only a few studies have shown that ozone has an effect on the stages of growth in herbaceous plants such as leafy vegetables. In the case of leafy vegetables such as Brassica (mustard, oilseed rape), there have been many studies related to ozone response based on crop or cultivars ( Abedi and Pakniyat, 2010 ; Singh et al., 2011 ). When growing lettuce in a PFAL, it is important to monitor the ozone response as an elicitor because lettuce has a high economic and commercial value.…”
Section: Introductionmentioning
confidence: 99%